Contribution of Tea Root Reinforcement to Soil Shear Strength on Slope Stability - Mukhsin Mukhsin (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2018)
Roots played important role in the process of stabilizing the soil mass. The geo-mechanical and soil-hydrological aspects on the slope are determined by, one of it, the root reinforcement. The role of root branching series with diameter differentiation is greatly determining its tensile stress. The tensile stress from the interaction between the root and the soil, could it contribute to increasing the shear strength of the slope stability. The purpose of this research was to identify the tensile stress on root branching series that interacted with the soil and created additional cohesion as a shear strength contribution to the slope stability. Testing on the root pulling force was conducted on slope prototype with angle 30o to 40o and has been planted with tea vegetation. A tripod that was completed with strain gauge as the recording instrument was used. Testing was conducted on two and three root branching, also on each unit by observing the diameter. This testing method was done in saturated soil condition. The tensile stress result showed that increasing diameter of the tea root, an increase was noticed, and also result in the equation of TFr = 0.089e0.516d. Root diameter increase on two and three root branching to one unit of tea vegetation showed that the stress increase was significant. When observed, in the root diameter differentiation of 4 mm to 6 mm, the stress on two and three root branching and one unit of tea vegetation were respectively 5.94%, 12.30%, and 35.42%. The contribution of additional cohesion caused by root-soil interaction to soil shear strength apparently could increase slope stability.